2019
DOI: 10.1007/s11042-019-08175-y
|View full text |Cite
|
Sign up to set email alerts
|

Dilated temporal relational adversarial network for generic video summarization

Abstract: The large amount of videos popping up every day, make it more and more critical that key information within videos can be extracted and understood in a very short time. Video summarization, the task of finding the smallest subset of frames, which still conveys the whole story of a given video, is thus of great significance to improve efficiency of video understanding. We propose a novel Dilated Temporal Relational Generative Adversarial Network (DTR-GAN) to achieve frame-level video summarization. Given a vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Supervised methods [8,10,11,19,24,31,32,38,39,40,41,42,47] learn video summarization from labeled data consisting of raw videos and their corresponding groundtruth summary videos. Supervised methods tend to outperform unsupervised ones, since they can learn useful cues from ground truth summaries that are hard to capture with hand-crafted heuristics.…”
Section: Related Workmentioning
confidence: 99%
“…Supervised methods [8,10,11,19,24,31,32,38,39,40,41,42,47] learn video summarization from labeled data consisting of raw videos and their corresponding groundtruth summary videos. Supervised methods tend to outperform unsupervised ones, since they can learn useful cues from ground truth summaries that are hard to capture with hand-crafted heuristics.…”
Section: Related Workmentioning
confidence: 99%
“…A significant number of deep learning based frameworks have been explored recently in solving video summarization [3,22,24,26,28]. K. Zhang et al creatively applied LSTM in supervised video sequence labelling to model video temporal information with good performance [24].…”
Section: Related Workmentioning
confidence: 99%
“…K. Zhou et al showed that fully unsupervised learning can outperform many supervised methods by considering diversity and representativeness in reinforcement learning-based framework [28]. Y. Zhang et al introduced adversarial loss to video summarization which learns a dilated temporal relational generator and a discriminator with three-player loss [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Video/text summarization Existing models are either supervised or unsupervised. Unsupervised summarization models in video [9,31,40,41,43,50,52,54,55] and text [10,26,25,3] domains aim to identify a small subset of key units (video-segments/sentences) that preserve the global content of the input, e.g., using criteria like diversity and representativeness. In contrast, supervised video [13,15,16,42,49,51] and text [37,6,28,30,46] summarization methods solve the same problem by employing ground-truth summaries as training targets.…”
Section: Related Workmentioning
confidence: 99%